Question Number 215395 by mr W last updated on 05/Jan/25 | ||
![]() | ||
Commented by mr W last updated on 06/Jan/25 | ||
![]() | ||
$${a}\:{ball}\:{with}\:{mass}\:{m}\:{falls}\:{from}\:{the} \\ $$$${hight}\:{h}\:{and}\:{hits}\:{the}\:{end}\:{of}\:{the}\:{rod} \\ $$$${jutting}\:{out}\:{off}\:{the}\:{edge}\:{of}\:{a}\:{table}. \\ $$$${the}\:{length}\:{of}\:{the}\:{uniform}\:{rod}\:{with}\: \\ $$$${mass}\:{M}\:{is}\:{L}={a}+{b}\:\left({a}>{b}\right). \\ $$$$ \\ $$$$\left.\mathrm{1}\right)\:{find}\:{the}\:{maximum}\:{hight}\:{which} \\ $$$${the}\:{ball}\:{will}\:{reach}\:{after}\:{collision}. \\ $$$$ \\ $$$$\left.\mathrm{2}\right)\:{find}\:{the}\:{maximum}\:{hight}\:{which} \\ $$$${the}\:{rod}\:{will}\:{reach}\:{after}\:{collision}. \\ $$$$\left({supposed}\:{that}\:{the}\:{table}\:{is}\:{removed}\right. \\ $$$${away}\:{after}\:{the}\:{collision}\:{so}\:{that}\:{the} \\ $$$$\left.{rod}\:{can}\:{move}\:{freely}\right). \\ $$ | ||
Commented by ajfour last updated on 07/Jan/25 | ||
https://youtu.be/2O_ZoICD2Ss?si=r85hss2CP8u60lv6 Motion of charge in variable magnetic field | ||
Commented by mr W last updated on 07/Jan/25 | ||
Answered by mr W last updated on 07/Jan/25 | ||
![]() | ||
Commented by mr W last updated on 10/Jan/25 | ||
![]() | ||
Commented by mr W last updated on 10/Jan/25 | ||
![]() | ||
$${f}=\mu{N}=\mu{mg}\:\mathrm{cos}\:\theta \\ $$$${v}=\omega{r} \\ $$$${I}_{{p}} =\frac{\mathrm{2}{mr}^{\mathrm{2}} }{\mathrm{5}}+{mr}^{\mathrm{2}} =\frac{\mathrm{7}{mr}^{\mathrm{2}} }{\mathrm{5}} \\ $$$${mg}\left(\mathrm{sin}\:\theta+\mu\mathrm{cos}\:\theta\right){s}_{\mathrm{1}} =\frac{{mu}^{\mathrm{2}} }{\mathrm{2}}−\frac{\mathrm{1}}{\mathrm{2}}×\frac{\mathrm{7}{mr}^{\mathrm{2}} \omega^{\mathrm{2}} }{\mathrm{5}} \\ $$$$\Rightarrow{g}\left(\mathrm{sin}\:\theta+\mu\mathrm{cos}\:\theta\right){s}_{\mathrm{1}} =\frac{{u}^{\mathrm{2}} }{\mathrm{2}}−\frac{\mathrm{7}{r}^{\mathrm{2}} \omega^{\mathrm{2}} }{\mathrm{10}} \\ $$$${a}=\left(\mathrm{sin}\:\theta+\mu\:\mathrm{cos}\:\theta\right){g} \\ $$$$\alpha=\frac{{fr}}{{I}}=\frac{\mu{mgr}\:\mathrm{cos}\:\theta}{\frac{\mathrm{2}{mr}^{\mathrm{2}} }{\mathrm{5}}}=\frac{\mathrm{5}\mu{g}\:\mathrm{cos}\:\theta}{\mathrm{2}{r}} \\ $$$$\frac{{u}−{v}}{{a}}=\frac{{u}−{r}\omega}{\left(\mathrm{sin}\:\theta+\mu\:\mathrm{cos}\:\theta\right){g}}=\frac{\omega}{\alpha}=\frac{\mathrm{2}{r}\omega}{\mathrm{5}\mu{g}\:\mathrm{cos}\:\theta} \\ $$$$\frac{{u}−{r}\omega}{\mathrm{tan}\:\theta+\mu}=\frac{\mathrm{2}{r}\omega}{\mathrm{5}\mu} \\ $$$$\Rightarrow{r}\omega=\frac{\mathrm{5}\mu{u}}{\mathrm{7}\mu+\mathrm{2}\:\mathrm{tan}\:\theta} \\ $$$${g}\left(\mathrm{sin}\:\theta+\mu\mathrm{cos}\:\theta\right){s}_{\mathrm{1}} =\frac{{u}^{\mathrm{2}} }{\mathrm{2}}−\frac{\mathrm{7}}{\mathrm{10}}×\left(\frac{\mathrm{5}\mu{u}}{\mathrm{7}\mu+\mathrm{2}\:\mathrm{tan}\:\theta}\right)^{\mathrm{2}} \\ $$$${s}_{\mathrm{1}} =\frac{\left[\mathrm{1}−\frac{\mathrm{35}\mu^{\mathrm{2}} }{\left(\mathrm{7}\mu+\mathrm{2}\:\mathrm{tan}\:\theta\right)^{\mathrm{2}} }\right]{u}^{\mathrm{2}} }{\mathrm{2}{g}\left(\mathrm{sin}\:\theta+\mu\:\mathrm{cos}\:\theta\right)} \\ $$$${mgs}_{\mathrm{2}} \mathrm{sin}\:\theta=\frac{\mathrm{1}}{\mathrm{2}}×\frac{\mathrm{7}{mr}^{\mathrm{2}} \omega^{\mathrm{2}} }{\mathrm{5}} \\ $$$${s}_{\mathrm{2}} =\frac{\mathrm{7}{r}^{\mathrm{2}} \omega^{\mathrm{2}} }{\mathrm{10}{g}\:\mathrm{sin}\:\theta}=\frac{\mathrm{7}}{\mathrm{10}{g}\:\mathrm{sin}\:\theta}×\left(\frac{\mathrm{5}\mu{u}}{\mathrm{7}\mu+\mathrm{2}\:\mathrm{tan}\:\theta}\right)^{\mathrm{2}} \\ $$$$\Rightarrow{s}_{\mathrm{2}} =\frac{\mathrm{35}\mu^{\mathrm{2}} {u}^{\mathrm{2}} }{\mathrm{2}{g}\:\mathrm{sin}\:\theta\:\left(\mathrm{7}\mu+\mathrm{2}\:\mathrm{tan}\:\theta\right)^{\mathrm{2}} } \\ $$$${s}={s}_{\mathrm{1}} +{s}_{\mathrm{2}} \\ $$$$\Rightarrow{s}=\frac{\left[\mathrm{1}+\frac{\mathrm{35}\mu^{\mathrm{2}} }{\left(\mathrm{7}\mu+\mathrm{2}\:\mathrm{tan}\:\theta\right)^{\mathrm{2}} }\right]{u}^{\mathrm{2}} }{\mathrm{2}{g}\left(\mathrm{sin}\:\theta+\mu\:\mathrm{cos}\:\theta\right)}+\frac{\mathrm{35}\mu^{\mathrm{2}} {u}^{\mathrm{2}} }{\mathrm{2}{g}\:\mathrm{sin}\:\theta\:\left(\mathrm{7}\mu+\mathrm{2}\:\mathrm{tan}\:\theta\right)^{\mathrm{2}} } \\ $$ | ||
Commented by mr W last updated on 08/Jan/25 | ||
![]() | ||
$${u}=\sqrt{\mathrm{2}{gh}} \\ $$$${mv}={J}_{\mathrm{1}} −{mu} \\ $$$${V}=\frac{\left({a}−{b}\right)\omega}{\mathrm{2}} \\ $$$${MV}={J}_{\mathrm{2}} −{J}_{\mathrm{1}} \\ $$$$\frac{{M}\left({a}−{b}\right)\omega}{\mathrm{2}}={J}_{\mathrm{2}} −{m}\left({v}+{u}\right) \\ $$$${J}_{\mathrm{2}} =\frac{{M}\left({a}−{b}\right)\omega}{\mathrm{2}}+{m}\left({v}+{u}\right) \\ $$$$\frac{{M}\left({a}+{b}\right)^{\mathrm{2}} \omega}{\mathrm{12}}={J}_{\mathrm{1}} {b}−\frac{\left({a}−{b}\right){J}_{\mathrm{2}} }{\mathrm{2}} \\ $$$$\frac{{M}\left({a}+{b}\right)^{\mathrm{2}} \omega}{\mathrm{12}}={m}\left({v}+{u}\right){b}−\frac{\left({a}−{b}\right)}{\mathrm{2}}\left[\frac{{M}\left({a}−{b}\right)\omega}{\mathrm{2}}+{m}\left({v}+{u}\right)\right] \\ $$$$\frac{\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{ab}\right){M}\omega}{\mathrm{3}}=\frac{{m}\left(\mathrm{3}{b}−{a}\right)\left({v}+{u}\right)}{\mathrm{2}} \\ $$$$\Rightarrow{v}=\frac{\mathrm{2}{M}\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{ab}\right)\omega}{\mathrm{3}{m}\left(\mathrm{3}{b}−{a}\right)}−{u} \\ $$$$\frac{{m}\left({u}^{\mathrm{2}} −{v}^{\mathrm{2}} \right)}{\mathrm{2}}=\frac{{MV}^{\mathrm{2}} }{\mathrm{2}}+\frac{\mathrm{1}}{\mathrm{2}}×\frac{{M}\left({a}+{b}\right)^{\mathrm{2}} \omega^{\mathrm{2}} }{\mathrm{12}} \\ $$$$\frac{{m}\left({u}^{\mathrm{2}} −{v}^{\mathrm{2}} \right)}{{M}}=\frac{\left({a}−{b}\right)^{\mathrm{2}} \omega^{\mathrm{2}} }{\mathrm{4}}+\frac{\left({a}+{b}\right)^{\mathrm{2}} \omega^{\mathrm{2}} }{\mathrm{12}} \\ $$$${v}^{\mathrm{2}} ={u}^{\mathrm{2}} −\frac{{M}\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{ab}\right)\omega^{\mathrm{2}} }{\mathrm{3}{m}} \\ $$$${with}\:\mu=\frac{{m}}{{M}} \\ $$$$\left[\frac{\mathrm{2}\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{ab}\right)\omega}{\mathrm{3}\mu\left(\mathrm{3}{b}−{a}\right)}−{u}\right]^{\mathrm{2}} ={u}^{\mathrm{2}} −\frac{\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{ab}\right)\omega^{\mathrm{2}} }{\mathrm{3}\mu} \\ $$$$\Rightarrow\omega=\frac{\mathrm{12}\mu\left(\mathrm{3}{b}−{a}\right){u}}{\mathrm{4}\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{ab}\right)+\mathrm{3}\mu\left(\mathrm{3}{b}−{a}\right)^{\mathrm{2}} } \\ $$$${x}_{{A}} =\frac{\left({a}+{b}\right)\mathrm{cos}\:\left(\omega{t}\right)}{\mathrm{2}} \\ $$$${y}_{{A}} ={Vt}−\frac{{gt}^{\mathrm{2}} }{\mathrm{2}}+\frac{\left({a}+{b}\right)\mathrm{sin}\:\left(\omega{t}\right)}{\mathrm{2}} \\ $$$${y}_{{A}} =\frac{\left({a}−{b}\right)\omega{t}}{\mathrm{2}}−\frac{{gt}^{\mathrm{2}} }{\mathrm{2}}+\frac{\left({a}+{b}\right)\mathrm{sin}\:\left(\omega{t}\right)}{\mathrm{2}} \\ $$$${v}=\left[\frac{\mathrm{8}}{\mathrm{4}+\frac{\mathrm{3}\mu\left(\mathrm{3}{b}−{a}\right)^{\mathrm{2}} }{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{ab}}}−\mathrm{1}\right]{u} \\ $$$${v}=\mathrm{0}\:{when}\:\mu=\frac{\mathrm{4}\left({a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{ab}\right)}{\mathrm{3}\left(\mathrm{3}{b}−{a}\right)^{\mathrm{2}} } \\ $$$${for}\:{v}>\mathrm{0},\:{i}.{e}.\:{when}\:{the}\:{ball}\:{rebounds} \\ $$$${from}\:{the}\:{rod},\:{it}\:{can}\:{reach}\:{a}\:{maximum} \\ $$$${hight}\:{h}_{{max}} \:{with} \\ $$$$\frac{{h}_{{max}} }{{h}}=\left(\frac{{v}}{{u}}\right)^{\mathrm{2}} =\left[\frac{\mathrm{8}}{\mathrm{4}+\frac{\mathrm{3}\mu\left(\mathrm{3}{b}−{a}\right)^{\mathrm{2}} }{{a}^{\mathrm{2}} +{b}^{\mathrm{2}} −{ab}}}−\mathrm{1}\right]^{\mathrm{2}} \\ $$$${with}\:\frac{{b}}{{a}}=\lambda \\ $$$$\frac{{h}_{{max}} }{{h}}=\left[\frac{\mathrm{8}}{\mathrm{4}+\frac{\mathrm{3}\mu\left(\mathrm{3}\lambda−\mathrm{1}\right)^{\mathrm{2}} }{\lambda^{\mathrm{2}} −\lambda+\mathrm{1}}}−\mathrm{1}\right]^{\mathrm{2}} \\ $$ | ||
Commented by ajfour last updated on 08/Jan/25 | ||
https://youtu.be/3wiUgK_riz8?si=pKPRqyotoxf-pwhm How far up the incline does solid ball reach? | ||
Commented by mr W last updated on 08/Jan/25 | ||
Commented by mr W last updated on 09/Jan/25 | ||
![]() | ||
Commented by mr W last updated on 09/Jan/25 | ||
![]() | ||
Commented by mr W last updated on 09/Jan/25 | ||
![]() | ||
Commented by mr W last updated on 09/Jan/25 | ||
![]() | ||
Commented by ajfour last updated on 10/Jan/25 | ||
Thanks for this. by the way any error/blunder in my video lecture for this question sir, did you notice? | ||
Commented by mr W last updated on 10/Jan/25 | ||
![]() | ||
$${i}\:{got}\:{x}={s}_{\mathrm{1}} =\frac{\left[\mathrm{1}−\frac{\mathrm{35}\mu^{\mathrm{2}} }{\left(\mathrm{7}\mu+\mathrm{2}\:\mathrm{tan}\:\theta\right)^{\mathrm{2}} }\right]{u}^{\mathrm{2}} }{\mathrm{2}{g}\left(\mathrm{sin}\:\theta+\mu\:\mathrm{cos}\:\theta\right)} \\ $$$${while}\:{you}\:{got} \\ $$$${x}=\frac{\left[\mathrm{1}−\frac{\mathrm{25}\mu^{\mathrm{2}} }{\left(\mathrm{7}\mu+\mathrm{2}\:\mathrm{tan}\:\theta\right)^{\mathrm{2}} }\right]{u}^{\mathrm{2}} }{\mathrm{2}{g}\left(\mathrm{sin}\:\theta+\mu\:\mathrm{cos}\:\theta\right)} \\ $$ | ||
Commented by ajfour last updated on 11/Jan/25 | ||
![]() | ||
$$\Rightarrow{g}\left(\mathrm{sin}\:\theta+\underline{\mu\mathrm{cos}\:\theta}\right){s}_{\mathrm{1}} =\frac{{u}^{\mathrm{2}} }{\mathrm{2}}−\frac{\mathrm{7}{r}^{\mathrm{2}} \omega^{\mathrm{2}} }{\mathrm{10}} \\ $$$${Point}\:{of}\:{application}\:{of}\:{friction}\:{force}\:{moves} \\ $$$${through}\:{s}_{\mathrm{1}} −{r}\boldsymbol{\phi}\:\:{so}\:\:{above}\:{eq}.\:{should}\:{be}: \\ $$$${g}\left(\mathrm{sin}\:\theta\right){s}_{\mathrm{1}} +\left(\mu{g}\mathrm{cos}\:\theta\right)\left({s}_{\mathrm{1}} −{r}\boldsymbol{\phi}\right)=\frac{{u}^{\mathrm{2}} }{\mathrm{2}}−\frac{\mathrm{7}{r}^{\mathrm{2}} \omega^{\mathrm{2}} }{\mathrm{10}} \\ $$$${i}\:{mean}\:{incline}\:{sees}\:{sphere}\:{surface}\: \\ $$$${has}\:{rubbed}\:{past}\:{this}\:{length}\:=\:{s}_{\mathrm{1}} −{r}\boldsymbol{\phi} \\ $$$$\frac{{v}^{\mathrm{2}} }{{r}^{\mathrm{2}} }=\omega^{\mathrm{2}} =\mathrm{2}\left(\frac{\mu{mgr}\mathrm{cos}\:\theta}{\frac{\mathrm{2}}{\mathrm{5}}{mr}^{\mathrm{2}} }\right)\boldsymbol{\phi} \\ $$$$\frac{{v}^{\mathrm{2}} }{{r}^{\mathrm{2}} }=\omega^{\mathrm{2}} =\left(\frac{\mathrm{5}\mu{g}}{{r}}\mathrm{cos}\:\theta\right)\phi \\ $$$$\mu{rg}\boldsymbol{\phi}\mathrm{cos}\:\theta=\frac{{v}^{\mathrm{2}} }{\mathrm{5}}=\frac{\omega^{\mathrm{2}} {r}^{\mathrm{2}} }{\mathrm{5}}\:\:\:\:\:\:\:\:{hence} \\ $$$${s}_{\mathrm{1}} \left(\mathrm{sin}\:\theta+\mu\mathrm{cos}\:\theta\right){g}−\frac{\mathrm{2}\omega^{\mathrm{2}} {r}^{\mathrm{2}} }{\mathrm{10}}=\frac{{u}^{\mathrm{2}} }{\mathrm{2}}−\frac{\mathrm{7}\omega^{\mathrm{2}} {r}^{\mathrm{2}} }{\mathrm{10}} \\ $$$${s}_{\mathrm{1}} =\frac{{u}^{\mathrm{2}} −\omega^{\mathrm{2}} {r}^{\mathrm{2}} }{\mathrm{2}{g}\left(\mathrm{sin}\:\theta+\mu\mathrm{cos}\:\theta\right)} \\ $$$${now}\:\:{as}\:\:{r}\omega=\frac{\mathrm{5}\mu{u}}{\mathrm{7}\mu+\mathrm{2}\:\mathrm{tan}\:\theta} \\ $$$${s}_{\mathrm{1}} =\frac{\left[\mathrm{1}−\frac{\mathrm{25}\mu^{\mathrm{2}} }{\left(\mathrm{7}\mu+\mathrm{2tan}\:\theta\right)^{\mathrm{2}} }\right]{u}^{\mathrm{2}} }{\mathrm{2}{g}\left(\mathrm{sin}\:\theta+\mu\mathrm{cos}\:\theta\right)}\:\:\:\bigstar \\ $$$${Along}\:{this}\:{approach}\:{i}\:{would}\:{get}\:{this},\:{sir}! \\ $$ | ||
Commented by mr W last updated on 11/Jan/25 | ||
![]() | ||
$${you}\:{are}\:{right}\:{sir},\:{thanks}\:{alot}! \\ $$ | ||